Patents and Technological Progress in a Globalized World
XXX, 910 p.
Keywords: In the last two decades, accelerating technological progress, increasing economic globalization and the proliferation of international agreements have created new challenges for intellectual property law. In this collection of articles in honor of Professor Joseph Straus, more than 60 scholars and practitioners from the Americas, Asia and Europe provide legal, economic and policy perspectives on these challenges, with a particular focus on the challenges facing the modern patent system. Among the many topics addressed are the rapid development of specific technical fields such as biotechnology, the relationship of exclusive rights and competition, and the application of territorially limited IP laws in cross-border scenarios.